Strengthening of RC beams by iron-based shape memory alloy bars embedded in a shotcrete layer. (15th June 2016) - Shahverdi, Moslem; Czaderski, Christoph; Annen, Philipp; Motavalli, Masoud
Highlights: Manufacturing of iron-based shape memory alloy (Fe-SMA) ribbed bars. Application demonstration of Fe-SMA bars embedded in shotcrete layer for strengthening RC beams. Activation of long Fe-SMA ribbed bars by resistive heating to prestress RC beams. Experimental investigation of three large scale RC beams. Abstract: Shape memory alloys (SMAs) have the special property of returning to their initial shape upon heating which is called shape memory effect (SME). If the returning to the initial shape is prevented by a mechanical fixation, a prestress develops in the SMA due to the SME property. In the form of ribbed bars, the SMAs can therefore be used for the strengthening and stiffening of reinforced concrete (RC) structures. In particular, the recently developed iron-based shape memory alloy (Fe-SMA) with the composition of Fe–17Mn–5Si–10Cr–4Ni–1VC (mass-%) shows promising properties with regard to potential applications in civil engineering. In the framework of this paper, application of the recently developed ribbed Fe-SMA bars embedded in a shotcrete layer to strengthen RC structure is presented. Three beams were experimentally examined to demonstrate the application of this strengthening method. The flexural behaviors of the beams were investigated during activation and in a four-point bending loading test up to failure. Two of the beams were prestressed with ribbed Fe-SMA bars embedded in an additionally applied shotcrete layer. The third beam had normal steel reinforcement bars in the shotcrete layer and acted as the reference beam. The behavior at the serviceability stage was significantly improved by the prestressed Fe-SMA bars. The cracking load increased with this method compared with the reference beam. The results showed that the application of ribbed Fe-SMA bars embedded in a newly applied shotcrete layer on the bottom side of RC beams was successful and the strengthening technique worked well.